4 - Negotiating Nation-building and Citizenship through the Truth and Reconciliation Committee’s ‘Dramatic’ Spheres: A Reading of Two Post-apartheid Plays - Mekusi, Busuyi (Africa Development, 2021)
Having a voice, either at the level of the individual or the community, has been one of the atavistic ways of defining or asserting humanity. This allows for the inscription of the twin-capped hegemony of successes or victories and frustrations at both the private locus and the public sphere. The disruptions of this possibility by rifts between natives in pre-colonial South Africa were aggravated in the heat of the colonial suppression it suffered, and was compounded by the operation of apartheid rule. By reason of this misrule, voices were suppressed, with a few cacophonies of dissention breaking forth. The culmination of these disenchantments into the demise of apartheid significantly presaged the need for reconstruction and redefinition of citizenship and cohabitation, and hence the necessity for establishing a public sphere, or put alternatively, a public domain in the form of the Archbishop Desmond Tutu’s Truth and Reconciliation Commission. This paper, therefore, seeks to interrogate the dramatic world(s) created using the material properties of the TRC in John Kani’s Nothing but the Truth and Zakes Mda’s The Bells of Amersfoort. The paper argues that the domination and manipulation of this public realm by the state at the expense of the individual is not only counterproductive, but constitutes a denial of the relevance of such spheres. The paper, going by indices in the plays, therefore, concludes that every individual should not only be: given a voice, and be heard, but be allowed equal unbiased participation. Otherwise, the public sphere would not just be impotent, but the idea of nation-building and desirable citizenship would be a mere ruse.